Anticancer activity of ruthenium and osmium cyclometalated compounds: identification of ABCB1 and EGFR as resistance mechanisms. Issue 3 (9th December 2019) - Licona, Cynthia; Delhorme, Jean-Baptiste; Riegel, Gilles; Vidimar, Vania; Cerón-Camacho, Ricardo; Boff, Bastien; Venkatasamy, Aina; Tomasetto, Catherine; da Silva Figueiredo Celestino Gomes, Priscila; Rognan, Didier; Freund, Jean-Noel; Le Lagadec, Ronan; et al.
Abstract : Switching from ruthenium to osmium reduces sensitivity towards ABCB1 resistance for cyclometalated anticancer drugs. Abstract : Ruthenium and osmium complexes have been shown to bypass several resistance mechanisms of platinum anticancer drugs, suggesting that they might represent therapeutic alternatives. However, the resistance mechanisms that may alter the cytotoxicity of ruthenium and osmium complexes have not been identified yet. Here we investigated the mechanisms governing the variability in the cytotoxicity of two ruthenium cyclometalated compounds and their osmium equivalents. We characterized their anticancer properties in vitro and in vivo, and we developed a 4-step approach to identify genes involved in their sensibility/resistance by correlating their cytotoxicity measures with transcriptomic data of 60 cancer cell lines. As previously observed for ruthenium complexes, we showed that osmium compounds target the endoplasmic reticulum stress pathway and that their activity was not hindered by mutation in the tumor suppressor gene TP53. Then, we identified multiple sensibility/resistance genes that correlated with the cytotoxicity of cyclometalated compounds. Docking and functional studies demonstrated that inhibition of some of these resistance mechanisms, namely ABCB1 export and EGFR expression, improved the activity of cyclometalated complexes. Interestingly, switching from ruthenium to osmium favored cytotoxicity while reducing sensibility to the ABCB1 export mechanism. In summary, this study represents the first comprehensive investigation of the resistance mechanisms that alter the biological activity of ruthenium or osmium complexes, and identifies some of the chemical determinants that are important for their activity.